Model Insentif Finansial Dalam Meningkatkan Kinerja - Sulistiyani Sutarlan; Kurnia Budi Dermawan (Journal of Business and Economics Research (JBE), 2022)
The company in doing work tries to improve performance well, therefore the company provides appropriate financial incentives and work life balance for employees in order to improve the quality and quantity of work. This study aims to examine the effect of financial incentives and work life balance in improving performance through organizational commitment. The research method is to apply the SPSS method with a total of 85 respondents. The results of data processing show that financial incentives and work life balances increase performance through organizational commitment.